Pengembangan E-Modul Menggunakan 3D Pageflip Profesional Pada Materi Puisi Di Kelas X SMK Negeri 2 Gunungsitoli - Syukur Jernih Hati Gulo; Noveri Amal Jaya Harefa (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to develop e-modules using 3D Pageflip Professional on Poetry Material in Class X SMK Negeri 2 Gunungsitoli. This type of research is development research. The development model used is the 4D model. The first stage in the 4D model is the define stage carried out by researchers in the field. The second is design (design) carried out after finding the problems that have been defined in the initial stage. This design stage aims to design an e-module media that can be used in learning. The third stage is develop (development) carried out by obtaining a product feasibility value validated by material experts, linguists, and media experts.  And the fourth stage of desseminate (dissemination) is the spread of product development, but given the limited costs, it only reaches the development stage. Based on the results of the study, the developed e-module has been tested highly valid by material validators at 95.96%, linguists at 85%, and media experts at 98.75%. Furthermore, the e-module is also very practical to be used by students with a practicality percentage of 86.4%. The e-module was also effective with a percentage of classical completeness of 85.72%.